WAYS TO DEVELOP BANKING ECOSYSTEMS IN UZBEKISTAN - Shamshiyev Sardor Zokir ugli (The Conference Hub, 2025)
In the context of a developing market, political events and their economic consequences, the transition to a new technological regime, and increased competition create difficulties for all financial and credit institutions. Leading financial and credit institutions of the world are taking active measures to adapt to new conditions, which will form new standards in the banking business.